Notices (Blackfriars, 1940)
PARABLES AND ALLEGORIES FROM THE BIBLE. Arranged by the Dominicans of Woodchester, with drawing by Sister Anscar, O.P. PIUS XII, PRIEST AND STATESMAN. By Kees van Hoek. LA PENSÉE SOCIALE DE S.S. PIE XII. By Albert Muller, S.J.